2019
DOI: 10.1029/2018wr023703
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Pathways, Processes, and Timing in an Agricultural Karst System: Development and Application of a Numerical Model

Abstract: Nitrogen (N) contamination within agricultural‐karst landscapes and aquifers is widely reported; however, the complex hydrological pathways of karst make N fate difficult to ascertain. We developed a hydrologic and N numerical model for agricultural‐karst, including simulation of soil, epikarst, phreatic, and quick flow pathways as well as biochemical processes such as nitrification, mineralization, and denitrification. We tested the model on four years of nitrate (NO3−) data collected from a phreatic conduit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 97 publications
6
100
1
Order By: Relevance
“…For context, we compare with a mature karst system 21 km from our study watershed (Royal Spring basin). For Royal Spring, three distinguishable hydrologic reservoirs were identified in the master recession curve, with coefficients of 0.50, 0.15, and 0.05 day −1 reflecting the quick, intermediate, and slow flow paths, respectively (Husic, Fox, Ford, et al, ). Regarding slow flow, our results found a master recession coefficient of 0.07 day −1 suggesting 75% of flow in the watershed on an annual basis is governed by recharge through low permeability matrix pores and small fissures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For context, we compare with a mature karst system 21 km from our study watershed (Royal Spring basin). For Royal Spring, three distinguishable hydrologic reservoirs were identified in the master recession curve, with coefficients of 0.50, 0.15, and 0.05 day −1 reflecting the quick, intermediate, and slow flow paths, respectively (Husic, Fox, Ford, et al, ). Regarding slow flow, our results found a master recession coefficient of 0.07 day −1 suggesting 75% of flow in the watershed on an annual basis is governed by recharge through low permeability matrix pores and small fissures.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding upland dynamics, recent advancements in techniques to quantify karst hydrologic pathways has led to a conceptualization of karst drainage as a series of reservoirs characterized by quick, intermediate, and slow flow pathways (Husic, Fox, Adams, et al, ; Husic, Fox, Ford, et al, ; Rimmer & Hartmann, ). Quickflow in karst watersheds reflects short residence time water originating from sinkholes, swallets, estavelles, and conduits (Pronk, Goldscheider, Zopfi, & Zwahlen, ; White, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While further attenuation is possible in the vadose zone as septic effluent leaves the drainfield (De & Toor, 2015) and reductions in N concentrations of 40% as effluent moves below the drainfield have been observed , we did not consider additional biogeochemical losses of septic leachate in the vadose zone as further attenuation is highly variable (CV = 118%; Katz et al, 2010) and losses are not always observed (Morales et al, 2016). A numerical model in an agricultural karst landscape also found much larger denitrification in the soil compared to epikarst (e.g., vadose zone) (Husic et al, 2019).…”
Section: Net Inputs Leached Below the Root Zone (L L ) And Recharged mentioning
confidence: 98%